STUDI DESKRIPTIF HASIL KARYA GAMBAR EKSPRESI DUA DIMENSI PADA PEMBELAJARAN SENI BUDAYA DAN KETERAMPILAN SISWA KELAS III SD NEGERI 48 KOTA BENGKULU - Ryanto, Hastomo Danu; Hasnawati, Hasnawati; Anggraini, Dwi (JURIDIKDAS, 2020)
This study aims to describe the work of two-dimensional expression drawings on the learning of cultural arts and skills of third grade students at SD Negeri 48 Bengkulu City. This type of research is a qualitative descriptive study, with participant observation techniques. The subjects of this study were all grade III students of 48 public elementary schools in Bengkulu city, totaling 19 students. The research instrument used was a human instrument, using interview guidelines, observation guidelines, and documentation guidelines. Data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques used are the results of the work that has been done by analyzing the data then reduced, display, and draw conclusions. The results of his research are from 19 works that have been made by students there are 5 styles found. Starting from the Structural Form drawing style that is characterized by the use of geometric shapes, Impressionism that is impressed with the texture interpretation of the colors taken from the effects of light, to the Romantic style of images relating to children's fantasies. Other drawing styles such as Lyrical, and Rhythmical Pattern are also found in the expressions of students' work. The use of striking colors in the Lyrical style signifies the nature of the child who wants to stand out among other friends. This trait is often addressed by girls usually through the colors that are etched into the picture. In addition, in a pattern of images that are repeated or Rhythmical Pattern is a form of emotional growth of a developing child